Morphological and molecular characterization of Heterosaccus papillosus Boschma, 1933 (Rhizocephala: Sacculinidae) and its effects on the swimming crab Charybdis anisodon De Haan, 1850 (Decapoda: Portunidae) in Nha Trang Bay, Vietnam - Oanh, Le Thi Kieu; Hoang, Anh Thi Ngoc; Vu, Thanh Quyet; Ha, Vo Thi; Tran, Sang Quang; Truong, Oanh Thi; Glenner, Henrik; Dang, Binh Thuy (Zootaxa, 2025)
Rhizocephala parasites, particularly Heterosaccus papillosus (Boschma), profoundly affect the morphology and physiology of their crustacean hosts, including the economically valuable swimming crab Charybdis anisodon (De Haan). This study provides a comprehensive analysis of H. papillosus in Vietnam, integrating detailed morphological description with molecular phylogenetic analysis using 18S rDNA and COI mtDNA. We confirm the parasite’s identity but uncover a substantial COI mtDNA divergence compared to GenBank sequences. This study documented an 11% infection rate, with host sex and size influencing prevalence. Notably, H. papillosus induced significant morphological modifications in C. anisodon, including abdominal segment expansion in males and pleopod degeneration in both sexes. These results emphasize the need for integrated taxonomic approaches and highlight the substantial impact of rhizocephalan parasitism on economically significant crab populations.